- Ratios and Unit Rates
- Home
- Writing Ratios Using Different Notations
- Writing Ratios for Real-World Situations
- Identifying Statements that Describe a Ratio
- Simplifying a Ratio of Whole Numbers: Problem Type 1
- Simplifying a Ratio of Decimals
- Finding a Unit Price
- Using Tables to Compare Ratios
- Computing Unit Prices to Find the Better Buy
- Word Problem on Unit Rates Associated with Ratios of Whole Numbers: Decimal Answers
- Solving a Word Problem on Proportions Using a Unit Rate
- Solving a One-Step Word Problem Using the Formula d = rt
- Function Tables with One-Step Rules
- Finding Missing Values in a Table of Equivalent Ratios
- Using a Table of Equivalent Ratios to Find a Missing Quantity in a Ratio
- Writing an Equation to Represent a Proportional Relationship

- Selected Reading
- UPSC IAS Exams Notes
- Developer's Best Practices
- Questions and Answers
- Effective Resume Writing
- HR Interview Questions
- Computer Glossary
- Who is Who

# Function Tables with One-Step Rules Online Quiz

Following quiz provides Multiple Choice Questions (MCQs) related to **Function Tables with One-Step Rules**. You will have to read all the given answers and click over the correct answer. If you are not sure about the answer then you can check the answer using **Show Answer** button. You can use **Next Quiz** button to check new set of questions in the quiz.

**Q 1 - Determine what one-step rule is used in the function table below.**

In | Out |

12 | 20 |

15 | 23 |

18 | 26 |

### Answer : A

### Explanation

**Step 1:**

20 = 12 + 8; 23 = 15 + 8; 26 = 18 + 8; Out = In + 8

**Step 2:**

So, the rule is ‘Add 8’ to input to get output.

**Q 2 - Determine what one-step rule is used in the function table below.**

In | Out |

10 | 22 |

13 | 25 |

16 | 28 |

### Answer : C

### Explanation

**Step 1:**

22 = 10 + 12; 25 = 13 + 12; 28 = 16 + 12; Out = In + 12

**Step 2:**

So, the rule is ‘Add 12’ to input to get output.

**Q 3 - Determine what one-step rule is used in the function table below.**

In | Out |

15 | 21 |

18 | 24 |

21 | 27 |

### Answer : B

### Explanation

**Step 1:**

21 = 15 + 6; 24 = 18 + 6; 27 = 21 + 6; Out = In + 6

**Step 2:**

So, the rule is ‘Add 6’ to input to get output.

**Q 4 - Determine what one-step rule is used in the function table below.**

In | Out |

33 | 22 |

36 | 25 |

39 | 28 |

### Answer : D

### Explanation

**Step 1:**

22 = 33 − 11; 25 = 36 − 11; 28 = 39 − 11; Out = In − 11

**Step 2:**

So, the rule is ‘Subtract 11’ from input to get output.

**Q 5 - Determine what one-step rule is used in the function table below.**

In | Out |

13 | 20 |

16 | 23 |

19 | 26 |

### Answer : B

### Explanation

**Step 1:**

20 = 13 + 7; 23 = 16 + 7; 26 = 19 + 7; Out = In + 7

**Step 2:**

So, the rule is ‘Add 7’ to input to get output.

**Q 6 - Determine what one-step rule is used in the function table below.**

In | Out |

10 | 22 |

13 | 25 |

16 | 28 |

### Answer : C

### Explanation

**Step 1:**

22 = 10 + 12; 25 = 13 + 12; 28 = 16 + 12; Out = In + 12

**Step 2:**

So, the rule is ‘Add 12’ to input to get output.

**Q 7 - Determine what one-step rule is used in the function table below.**

In | Out |

15 | 21 |

18 | 24 |

21 | 27 |

### Answer : A

### Explanation

**Step 1:**

21 = 15 + 6; 24 = 18 + 6; 27 = 21 + 6; Out = In + 6

**Step 2:**

So, the rule is ‘Add 6’ to input to get output.

**Q 8 - Determine what one-step rule is used in the function table below.**

In | Out |

31 | 22 |

34 | 25 |

37 | 28 |

### Answer : D

### Explanation

**Step 1:**

22 = 31 − 9; 25 = 34 − 9; 28 = 37 − 9; Out = In – 9

**Step 2:**

So, the rule is ‘Subtract 9’ from input to get output.

**Step 3:**

**Q 9 - Determine what one-step rule is used in the function table below.**

In | Out |

21 | 35 |

24 | 38 |

27 | 41 |

### Answer : B

### Explanation

**Step 1:**

35 = 21 + 14; 38 = 34 + 14; 41 = 27 + 14; Out = In + 14

**Step 2:**

So, the rule is ‘Add 14’ to input to get output.

**Q 10 - Determine what one-step rule is used in the function table below.**

In | Out |

22 | 11 |

27 | 16 |

32 | 21 |

### Answer : C

### Explanation

**Step 1:**

11 = 22 − 11; 16 = 27 − 11; 21 = 32 − 11; Out = In − 11

**Step 2:**

So, the rule is ‘Subtract 11’ from input to get output.